Cover Picture: Synergistically Directed Assembly of Aromatic Stacks Based Metal‐Organic Frameworks by Donor‐Acceptor and Coordination Interactions (Chin. J. Chem. 9/2019). Issue 9 (21st August 2019) - Wang, Xi; Zhang, Ying; Chang, Ze; Huang, Hui; Liu, Xiao‐Ting; Xu, Jialiang; Bu, Xian‐He
Abstract : The cover picture shows a synergistically directed assembly route towards novel multi‐component coordination architectures driven by aromatic donor‐acceptor and coordination interactions. The huge structural discrepancies between coronene donor present and absent experiments clearly prove the significance of aromatic donor‐accepter pairs and their inherent cooperation mechanism in these assembly processes. More details are discussed by Bu et al . on page 871–877. Abstract : The cover picture shows a synergistically directed assembly route towards novel multi‐component coordination architectures driven by aromatic donor‐acceptor and coordination interactions. The huge structural discrepancies between coronene donor present and absent experiments clearly prove the significance of aromatic donor‐accepter pairs and their inherent cooperation mechanism in these assembly processes. More details are discussed by Bu et al . on page 871–877.